(untitled) (DAPesquisa, 2020)
A conversation, a sharing of experiences. This is a set of five letters between researchers-artists-teachers. Estela Vale Villegas wrote the first one of them reporting her experience as a teacher-artist in her research of performance pedagogies. The content of her letter evoked a desire for dialogue between other women whose experience was similar. Therefore, Juliana Liconti, Ines Saber and Raquel Purper, willing to write her back, shared their methodologies and the challenges they face in classrooms, at school and at the university. In addition to being researchers-artists-teachers, their interests in the field of performance are intertwined, whether they are thinking about the scene, the teaching-learning experience or the possibilities of academic writing.